Impact Of Nutritional Requirements For Transgender Health Care - An Observational Study (International Journal of Food and Nutritional Sciences, 2023)
There currently are no specific nutrition guidelines for transgender patients. While evidence is limited to using gender identity for estimating nutrition requirements, research has shown testosterone hormone therapy to change metabolic needs. The goal of this study was to know more about the nutrition-related health disparities and barriers to adequate nutrition and health that transgender’s experience. The effort to assess (Questionnaire-based) can be conducted within the community to understand their nutritional needs specifically. Surveys can be used to gather qualitative and quantitative data on nutrition-related health discrepancies and barriers, as well as to identify potential interventions to reduce the discrepancies or barriers of transgender health care.It is clear that food insecurity, body image, nutrition knowledge and skills, dietary intake, and barriers to healthy eating and positive body image emerged and highlighted as a major theme in this study. Previously reviewed studies reveals that transgender have lower dietary intake, body imagebehaviours, and food insecurity. Hence, we can also [provide them with a proper nutrition education and awarenessprogramme to help shine them better in the society.